Adenosine plasma level and A2A adenosine receptor expression: correlation with laboratory tests in patients with neurally mediated syncope. Issue 11 (12th May 2012) - Deharo, Jean-Claude; Mechulan, Alexis; Giorgi, Roch; Franceschi, Frederic; Prevot, Sebastien; Peyrouse, Eric; Condo, Jocelyne; By, Youlet; Ruf, Jean; Brignole, Michelino; Guieu, Régis
Abstract : Objectives: The purpose of this study was to investigate the hypothesis that responses to the ATP test and head-up tilt test (HUT) may be correlated with different purinergic profiles. Design and setting: The ATP and HUT identify distinct subsets of patients with neurally mediated syncope (NMS). Adenosine and its A2A receptors (A2A R) may be implicated in the pathophysiology of NMS in patients with positive HUT. Nothing is known about the purinergic profile of patients with positive ATP. Patients and measures: This prospective study includes a consecutive series of patients with suspected NMS. All patients underwent both HUT and ATP. Before testing, samples were collected for measurement of baseline adenosine plasma level (APL) and expression. Results: A total of 46 patients (25 men and 21 women) with a mean age of 57±18 years were enrolled. The HUT test was positive in 27 patients and the ATP test in 20. Both tests were positive in 9 and negative in 8. High APL was associated with high probability of positive HUT while low APL was associated with high probability of positive ATP. Expression of A2A R was lower in patients with positive ATP than in those with positive HUT. Conclusion: These findings indicate that patients with NMS present different purinergic profiles and that responses to HUT and ATP are correlated with these profiles.